I’m Tired With The Task!: Gambaran Deskriptif Ketidakjujuran Akademik Pada Mahasiswa Prodi Psikologi Di Universitas X - Farisandy, Ellyana Dwi; Putri, Irfany (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2024)
This study aims to explore academic dishonesty in undergraduate students of Psychology Study Program at University X. The design used is a descriptive study. Sample technique using conventional sampling with a total of 182 undergraduate students of Psychology Study Program at University X. The measuring instrument used is the Academic Dishonesty (ADS) which was compiled by Ampuni et al. (2019) based on measurements of academic dishonesty from McCabe and Trevino (1993) and Stone et al. (2010). The results show that there are some undergraduate students who still practice academic dishonesty, like cheating, unauthorized collaboration, and plagiarism. Besides that, the tendency for academic dishonesty to be committed in undergraduate students of Psychology Study Program at University X is in the very high category when viewed from group norms. The majority of factors that cause undergraduate students to commit academic dishonesty come from internal factors, namely wanting to get higher grades and external factors, namely the existence of lecturers who give many assignments.